MODEL PENULISAN BUKU AJAR BIOLOGI SMA BERWAWASAN EKOLOGI DAN LOKAL UNTUK MENINGKATKAN KEPEDULIAN SISWA TERHADAP LINGKUNGAN - Achyani Achyani; Nuryani Y. Rustaman; Sri Redjeki; Devi Nandita Choesin (Bioedukasi Jurnal Pendidikan Biologi, 2010)
A study using Research and Development design was conducted to produce a model of Biology hand book writing which is ecology and local oriented as an effort to increase students’ care toward environment. The background of this research is the reality which is  still going on untill now that the awareness and care of the school graduatee toward the environement safety is still low. Besides, hard science instructional at school could not affect or intervene the graduatee’s characteristics, for instance in keeping the environment awareness. Meanwhile, there are many concepts of environment which had been taught through hard science especially biology, so in the researcher’s point of view, biology subject has strategic role to prevent or mitigate the environment disaster caused by human activities. The model was validated at beach  ecosystem. The analysis of the research result includes three aspects, namely: 1) text comprehension, 2) environment care attitude, and 3) handbook readibility. Based on the result of beach ecosystem data analysis, it was found that (1) there was a significant difference between experimental class and control class in the beach ecosystem which is shown by tcalculation > ttable (7.429 > 2.00); (2) there was strong correlation between students’ comprehension and attitude which is shown by coeficient correlation (r) 0.634. While the text readability test (Cloze test) shown  the readability of beach ecosystem text is 57,57% (moderate). Therefore, it can be concluded that all of the texts in the developed book are fit and proper for SMA students of grade X. Kata kunci:  Penulisan buku ajar, orientasi ekologi dan lokal, kepedulian terhadap  lingkungan.